1986
DOI: 10.2466/pms.1986.63.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Token Economy by Peer Tutors to Increase On-Task Physical Activity Time of Autistic Children

Abstract: The data generated in this study were graphed for visual inspection of the raw data and means. Of the 5 subjects, 4 improved their time on task on the balance beam in at least one of the intervention phases. The other subject did not improve during the intervention phases but, there was a positive slope in the final intervention phase which might have continued had the intervention been longer. Further study is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Although it has been demonstrated that the behavior of both non-humans and humans can be established and maintained by schedules of token reinforcement, there are very few empirical studies on the effects of token reinforcement on the behavior of young children with autism (Charlop-Christy & Haymes, 1998;Hung, 1977;Mangus, Henderson, & French, 1986). It may be particularly socially significant to investigate the use of token economies with individuals diagnosed with autism because, as has been suggested elsewhere, the initial development of conditioned reinforcers may be delayed in this population (e.g., Bijou & Ghezzi, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been demonstrated that the behavior of both non-humans and humans can be established and maintained by schedules of token reinforcement, there are very few empirical studies on the effects of token reinforcement on the behavior of young children with autism (Charlop-Christy & Haymes, 1998;Hung, 1977;Mangus, Henderson, & French, 1986). It may be particularly socially significant to investigate the use of token economies with individuals diagnosed with autism because, as has been suggested elsewhere, the initial development of conditioned reinforcers may be delayed in this population (e.g., Bijou & Ghezzi, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Changes including the addition of tokens and gradual increases in PA requirements were necessary to increase Marcelo's PA. Several studies have used token reinforcement to increase PA in typically developing children or adults with ASD (Croce & Horvat, 1992; Krentz et al., 2016; Patel et al., 2019), but we could identify only a single experimental study that used tokens to increase PA in children with ASD (Mangus et al., 1986). Thus, analyzing the effectiveness of using a token‐reinforcement system to increase PA in this population and whether effects maintain following their removal remains a valuable area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was employed with the child with hypersensitivities to prevent exclusion from the study. The procedure included a Brief Multiple-Stimulus Without Replacement (Brief MSWO) preference assessment and a token economy system together with gradually increasing the time wearing the fNIRS cap while gradually adding more optodes to the cap [20,21].…”
Section: Methodsmentioning
confidence: 99%